AQUEOUS LEAF EXTRACT OF ZIZIPHUS MAURITIANA IS POTENT ON CARBON TETRACHLORIDE-INDUCED LIVER DAMAGE IN ALBINO RATS - Gadanya, H. S.; Gadanya, M. A.; Ibrahim, I. M.; Wudil, A. M. (FUDMA JOURNAL OF SCIENCES, 2023)
Globally and locally there is an increase in burden of liver diseases arising from toxins, infectious and non-infectious conditions. This research work was aimed at studying the effects of aqueous leaf extract of Ziziphus mauritiana on Carbon Tetrachloride-induced liver damage in albino rats in comparison with currently used drug Livolin. Liver damage was induced by intramuscular injection of 120 mg/kg by weight of CCl4. The effects of aqueous leaves extract of Z. mauritiana were determined in groups of liver toxicity model rats. Different groups of rats (total of 36 rats) were administered with three different doses of aqueous leaves extract of Z. mauritiana (50 mg/kg, 100 mg/kg and 150 mg/kg), with assessment of liver functions indices at intervals of two and four weeks. The allocation was as follows: control group (6 rats), test-control (6 rats), 50 mg/Kg extract dose (6 rats), 100 mg/Kg extract dose (6 rats), 150 mg/kg dose (6 rats) and Livolin group (6 rats). Dose and time-dependent responses were found in the normalisation of the liver functions indices and histological, with the best performing extract (150 mg/kg) been less efficacious than Livolin in liver damage. The findings of this study shows that aqueous leaf extract of Z. mauritiana has phytochemical components that can potentially be useful in treating liver damage, with effects comparable to currently used pharmaceutical drugs like Livolin